2007
DOI: 10.1111/j.1467-9817.2007.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress sensitivity and reading performance in Spanish: A study with children

Abstract: This paper investigates the relationship between ability to detect changes in prosody and reading performance in Spanish. Participants were children aged 7-8 years. Their tasks consisted of reading words, reading non-words, stressing non-words and reproducing sequences of two, three or four non-words by pressing the corresponding keys on the computer keyboard. Non-word sequences were constructed with minimal non-word pairs differing in a single phoneme (/kúpi/ -/kúti/) or in the stress pattern (/mípa/ -/mipá/)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 26 publications
2
36
0
7
Order By: Relevance
“…Por tanto, la conciencia de los elementos suprasegmentales a nivel oral facilitaría la adecuada detección de los cambios de entonación que los signos de puntuación determinan y, por tanto, un buen rendimiento en la tarea. Tomados los resultados en su conjunto, parece que la conciencia del acento facilitaría la automaticidad en la decodificación, tal y como apuntan otros estudios (Gutiérrez-Palma y Palma- Reyes, 2007;Gutiérrez-Palma et al, 2009;Whalley y Hansen, 2006), mientras que las tareas de nombres compuestos y ritmo no lingüístico, donde entran en juego otros elementos prosódicos, tendrían mayor relación con la lectura prosódica, donde son clave las pausas y los cambios de entonación.…”
Section: Discussionunclassified
“…Por tanto, la conciencia de los elementos suprasegmentales a nivel oral facilitaría la adecuada detección de los cambios de entonación que los signos de puntuación determinan y, por tanto, un buen rendimiento en la tarea. Tomados los resultados en su conjunto, parece que la conciencia del acento facilitaría la automaticidad en la decodificación, tal y como apuntan otros estudios (Gutiérrez-Palma y Palma- Reyes, 2007;Gutiérrez-Palma et al, 2009;Whalley y Hansen, 2006), mientras que las tareas de nombres compuestos y ritmo no lingüístico, donde entran en juego otros elementos prosódicos, tendrían mayor relación con la lectura prosódica, donde son clave las pausas y los cambios de entonación.…”
Section: Discussionunclassified
“…More recently, Holliman, Wood, and Sheehy (2008) found that performance on this task could predict a significant amount of unique variance in word reading (3.8%) in a group of early readers after controlling for age, vocabulary, phoneme deletion, and rhyme detection ability (phonological awareness). Links between speech rhythm and word reading have also been demonstrated in other recent studies involving stress manipulation and sensitivity (Gutierrez-Palma & Reyes, 2007;Holliman, Wood, & Sheehy, 2009, in press;Wood & Terrell, 1998). Goswami et al (2002) investigated whether reading difficulties are associated with deficits in perceptual rhythmic timing.…”
Section: Speech Rhythm and Word Readingmentioning
confidence: 99%
“…Gutiérrez-Palma and Palma (2007) explored this relationship in children in 1st and 2nd year of Primary Education using the task designed by Dupoux et al (2001). The task involves discriminating between minimum pairs of pseudowords with a phonemic difference ("/kúpi/" vs. "/kúti/") or a prosodic difference ("/mípa/" vs. "/mipá/").…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the use of the stress mark is related to phonology but cannot be considered a true phoneme-to-grapheme conversion rule. Mastering the written mark of a stressed syllable is associated with knowing the word's prosodic characteristics (Gutiérrez-Palma and Palma 2007). In the same way as phonological awareness is related to reading and spelling acquisition, stress awareness (SA)-the ability to detect and manipulate the stress of words-may also be related to such acquisition, particularly in Spanish.…”
Section: Introductionmentioning
confidence: 99%